IB - "Sinha, B.P." (Delhi, 1973)
The first part, after a brief description of the public undertakings in general, takes up four organisations- two in private sector to discuss the various economic and pscychological indices of effiiciency in these organizations. The second part starts with a theoretical model in the context of the existing knowldege of the factors of human efficiecncy, and then presents the findings about the various facets of these organizations with reference to the model.
Keywords: Organization